2020
DOI: 10.1007/s11136-020-02436-2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling a preference-based index for EQ-5D-3L and EQ-5D-3L + Sleep using a Bayesian framework

Abstract: This is a repository copy of Modelling a preference-based index for EQ-5D-3L and EQ-5D-3L + Sleep using a Bayesian framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Of the 28 articles that were included, 3 articles were studies that identified possible bolt-ons (category A "identification or development of possible suitable bolt-ons"), [23][24][25] 13 articles were psychometric performance studies (category B "psychometric performance studies"), 8,26-37 and 6 articles were valuation studies of EQ-5D 1 bolt-on (category C "health state valuation studies"). 19,20,[38][39][40][41][42] Furthermore, 3 articles were categorized as both categories A and B, [43][44][45] and 3 articles as both categories A and C. 13,21,38 Study populations consisted of a healthy population (n = 17 articles: general public, 13,[19][20][21]24,25,27,30,36,38,[40][41][42][43] random households, 44,45 faculty members 39 ) and patients (n = 11 articles: individuals with a chronic condition, 23 visitors of an outpatient eye clinic, 26 cognitive impaired elderly patients, 18 patients with diabetes, 28 general injury patients, 29,31,35 patients listed for cataract surgery, 32,34 stroke patients, …”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 28 articles that were included, 3 articles were studies that identified possible bolt-ons (category A "identification or development of possible suitable bolt-ons"), [23][24][25] 13 articles were psychometric performance studies (category B "psychometric performance studies"), 8,26-37 and 6 articles were valuation studies of EQ-5D 1 bolt-on (category C "health state valuation studies"). 19,20,[38][39][40][41][42] Furthermore, 3 articles were categorized as both categories A and B, [43][44][45] and 3 articles as both categories A and C. 13,21,38 Study populations consisted of a healthy population (n = 17 articles: general public, 13,[19][20][21]24,25,27,30,36,38,[40][41][42][43] random households, 44,45 faculty members 39 ) and patients (n = 11 articles: individuals with a chronic condition, 23 visitors of an outpatient eye clinic, 26 cognitive impaired elderly patients, 18 patients with diabetes, 28 general injury patients, 29,31,35 patients listed for cataract surgery, 32,34 stroke patients, …”
Section: Study Characteristicsmentioning
confidence: 99%
“…21,38 For category B, 3 studies scored inadequate, 26,34,36 6 studies doubtful, 18,27,28,30,32,33 and 4 studies adequate. 29,31,35,37 Furthermore, 1 study in category C was judged inadequate, 19 3 studies doubtful, 21,38,39 1 study adequate, 41 and 4 studies very good. 13,20,40,42…”
Section: Quality Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychometric properties of the shortlisted EQ-5D-5 L bolton items should be examined quantitatively in future study, and valuation research may be conducted if appropriate bolt-on dimension(s) is validated. Despite the conventional EQ-VT valuation protocol may not be adopted for bolt-on valuation, a few publications had attempted to explore bolt-on valuation to facilitate economic evaluations [44][45][46]. The Hong Kong SAR community emphasized on both physical and mental health while some local HRQoL target could be covered by the original EQ-5D-5 L. However, other HRQoL targets such as 'eat well and 'sleep well' may not be described distinctively by the current EQ-5D system.…”
Section: Discussionmentioning
confidence: 99%